Register, Dialect, Convolution, and ‘Crosstalk’: Reflections on ‘ … the Zones of Influence and Hybridity Between Electroacoustic, Acousmatique Music, Techno, and IDM’. - Vaughan, Mike (Contemporary Music Review, 2016)
This paper explores the hybridisation of musical elements, particularly between those that foreground the use of technology across popular and art music. In its original form, the paper was presented to a conference Embracing rhythm … welcoming abstraction ( … on the zones of influence and hybridity between electroacoustic, acousmatique music, techno, and IDM) held at Salford University in November 2013, and was an intended overview of the topic. In this context, ‘ … zones of influence and hybridity’ between different repertoires that are generally understood to occupy different registral strata are viewed primarily as a form of environmental adaptation, expressed through the evolution of musical language. The paper also considers the motivations for attempting to reconcile, through creative practice, the conflicting meanings and aesthetic frameworks signified by different iconic musical materials and idiomatic compositional procedures. In examining these motivations and practices it draws on Barthes’ essay musica practica, to explore the significance to the creative artist of the network of relationships that link the different musics we compose or produce to the music that we might listen to or perform, or have encountered during academic training.